KESADARAN PERATURAN HUKUM AKAN PENGEMBANGAN INVESTASI DI BADAN USAHA MILIK DESA (BUMDES) KARANGREJO, KEDIRI - Moh. Maruf; Riyan Sisiawan Putra; Tamara Adillatirrusdah; Nurcahya Setiani Rahayu (LPPM Universitas Islam Darul 'Ulum Lamongan, 2024)
This research aims to describe how legal regulations awareness efforts will develop investment in village-owned enterprises (BUMDES) Karangrejo, Kediri. The method used in this research is a descriptive method with a qualitative approach. Data collection techniques were carried out by means of observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Furthermore, the data validity technique in this research uses triangulation. The results of this research explain that in this community service we can conclude that the legal basis that has been stated and applies in BUMDES Karangrejo, Kediri still does not apply well in the governance of BUMDES. Awareness of the law in investment development can still be said to be lacking, this can be seen from the many rights and obligations that are ignored when investing in BUMDES. Therefore, in this service activity, counseling is provided regarding the legal basis and basis of BUMDES and development of BUMDES investment, counseling regarding the rights and obligations of investors and BUMDES, and providing legal assistance to optimize BUMDES Karangejo, Kediri.